Ionic Liquids in Biocatalytic Oxidations: From Non-conventional Media to Non-solvent Applications - Fernandez-Alvaro, Elena; Dominguez de Maria, Pablo (Current Organic Chemistry, 2012)
Ionic Liquids (ILs) have emerged in the last decade as a novel technology to be applied in biocatalysis (among other areas of chemistry). Most of the work has focused on 2nd generation of ILs, a broad palette of tuneable solvents yet with still high prices for commercial applications. It is thus expected that such know-how will be transferred to 3rd generation of ILs and to deep-eutectic-solvents (DES), as the greener and more economic neoteric solvents for many future applications. In general, the use of a given IL must be triggered by firstly identifying an “added-value” that such derivative may bring to a certain application. In the field of oxidative biocatalysis, IL have been used as replacement of solvents for enzymatic reactions, as well as in more subtle applications as performance additives, protein stabilizers, in immobilization of enzymes, biosensors, etc. This article discusses the most relevant cases, providing emphasis, when possible, on the added-value that ILs may bring to the different areas, and that therefore justify their use.
Keywords: Solvents